ANALISIS DESKRIPTIF MOTIVASI BELAJAR MATEMATIKA SISWA MADRASAH TSANAWIYAH GORONTALO - Asriyati Nadjamuddin (Irfani, 2023)
Learning motivation is an essential factor influencing students’ engagement in mathematics learning. This study aims to analyze the level of mathematics learning motivation among students at MTsT Al Ishlah Gorontalo. The research employed a quantitative survey approach. The population consisted of 70 students, with a sample of 58 students from grades VII, VIII, and IX selected using a total sampling method. The instrument used was a mathematics learning motivation scale based on six indicators adapted from Uno, measured with a Likert scale (1–5). Data were analyzed descriptively to identify the distribution of students’ motivation levels. The findings revealed that no students were categorized as very low or low. A total of 19% of students fell into the moderate category, 72.4% into the high category, and 8.6% into the very high category. These results indicate that the majority of students possess strong motivation in learning mathematics, which serves as an essential asset in enhancing academic engagement. However, students in the moderate category require greater attention through creative, interactive, and contextual teaching strategies. In conclusion, students’ mathematics learning motivation at MTsT Al Ishlah Gorontalo is generally in the good to perfect category. Yet, continuous intervention is needed to maintain and further improve students’ motivation.